Voluntary disclosure of listed banks operating in Ghana - Koduah, Philemon Adjei (Faculty of Management Studies & Commerce, University of Jaffna, 2020)
Issues of voluntary disclosure have become relevant in Ghana after the Bank of Ghana took steps to rationalised banks in Ghana to strengthen the banking sector. The sudden collapse of some banks in Ghana may have raised some doubts among investors and other stakeholders with regards to the quality of information disclosed by banks in Ghana. It has therefore become important for banks in Ghana to improve the quality of financial information by setting up good governance structures and to provide adequate voluntary information in their annual reports to boost the confidence of investors and other stakeholders. This study examines the extent to which listed banks in Ghana voluntarily disclose information in their annual report for the 2018 period and to determine the differences in the types of information voluntarily disclosed by listed banks in Ghana. This study revealed an overall voluntary disclosure level mean of 0.6294 which was slightly above average. The Tukey post hoc test showed a statistical significant difference between strategic information and non-financial information as well as a statistical significant difference between strategic information and financial information. However, there is no statistical significant difference between non-financial information and financial information. The study concludes that adequate voluntary information must be provided in the annual reports of listed banks in Ghana to ensure transparency, consistency, reliability and comparability to influence the economic decision needs of investors and other users of accounting information.
Keywords: Voluntary disclosure; Strategic information; Non-financial information; Financial information; Listed banks in Ghana